Characteristic Differences Of Children Obesity And Overweight In Coastal Areas And Mountains - Asnidar; Haerati; Risky Razali (Comprehensive Health Care, 2020)
World Health Organization (WHO) in 2016 The rate of obesity in children in Indonesia was 11.5% and ranked 21st in the world. The purpose of this study was to find out the differences in characteristics of obese and overweight children in coastal and mountainous areas in Bulukumba District in 2018. The population in this study were obese and overweight children in 32 Bulukumba Junior High School, 18 Bulukumba Junior High School, and 14 Bulukumba Junior High School. The population in this study with the number of 423 respondents, the sample of this study were 71 respondents of the sampling technique used total sampling technique. This type of research is analytic research with a cross-sectional approach. The test used for differences in the characteristics of obese and overweight children in coastal and mountainous areas in Bulukumba Regency is the chi-square test with the results of the study that most of the students in high schools in the mountains who are obese are 17 respondents (44.7%) and those who are overweight (fat) 21 respondents (55.3). While most of the coastal areas were obese as many as 10 respondents (26.3%) and those who were overweight (fat) were 23 respondents (60.5%). The conclusion of this study is, "There are differences in the characteristics of obese and overweight children in the coastal and mountainous areas of Bulukumba District in 2018. The suggestions in this study can add library references and insights from students of Stikes Panrita Husada Bulukumba.